2023
DOI: 10.1111/os.13844
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Strategy and Outcomes of Full Endoscopic Lumbar Discectomy for Recurrent Lumbar Disk Herniation Following a Previous Full Endoscopic Lumbar Discectomy

Abstract: ObjectiveRecurrent lumbar disc herniation (RLDH) cannot be prevented after full endoscopic lumbar discectomy (FELD), and the optimal surgical treatment for RLDH after FELD remains controversial. The aim of the study was to suggest a surgical strategy for FELD to treat RLDH following a previous FELD and to present surgical outcomes.MethodsBetween February 2015 and March 2022, 68 patients with RLDH were surgically treated with FELD retrospectively. An original approach was suggested for the treatment of early re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In addition to the surgical technique itself, scarring and adhesions have a significant impact on reoperation after PETD. 7 Therefore, when both surgeries are able to remove the herniated disc, PEID is preferred to avoid scarring, reduce the risk of nerve damage, and avoid intraoperative disorientation due to the lack of typical bony markings, and the procedure and difficulty are similar to the initial surgery. Earlier studies by Ruetten et al have confirmed this opinion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the surgical technique itself, scarring and adhesions have a significant impact on reoperation after PETD. 7 Therefore, when both surgeries are able to remove the herniated disc, PEID is preferred to avoid scarring, reduce the risk of nerve damage, and avoid intraoperative disorientation due to the lack of typical bony markings, and the procedure and difficulty are similar to the initial surgery. Earlier studies by Ruetten et al have confirmed this opinion.…”
Section: Discussionmentioning
confidence: 99%
“…For herniation with lateral recess stenosis: In Ahn’s study, 12 PETD was useful for recurrent disc herniation in selected cases, but was successful in only 33.3% of patients with concomitant lateral recess stenosis. While in FEID, the inner part of the articular process and the lower edge of the lamina can provide a relatively normal window to expose the nerve root and avoid being interfered with by scarring, 7 so that the herniation can be excised well after partial laminectomy is performed as needed ( Figure.4 ).
Figure 3 A 42-year-old female presented for the first time with “low back pain with pain in the left lower extremity”, and the lumbar MR showed a disc herniation at L45 (A) .
…”
Section: Extremely Lateral Herniation Central Herniation or Lateral R...mentioning
confidence: 99%